Reconstructing caste: Post-colonialism, transnational activism and Dalit human rights - Zabiliūtė, Emilija (Acta Orientalia Vilnensia, 2010)
University of CopenhagenDalit organizations that focus on the Dalit human rights try to further their cause to the international level by adopting the international norms of human rights. By tackling the UN and the EU, they employ transnational activism strategies and attempt in this way to put the pressure on the Indian state. At the same time, they sustain caste identity that is rooted in the local Indian context. The latter is often primordialized, historicized and inseparable from the colonial constructs of caste and modernity formations. This article discusses these paradoxes by analysing the identity representations of the Dalits and their transnational strategies. Semi-structuredinterviews were conducted with two organizations, The National Campaign for Dalit Human Rights (NCDHR) in Delhi and the International Dalit Solidarity network (IDSN) in Copenhagen. Additionally, representational data like pamphlets, reports and videos was analysed. The article concludes by suggesting that caste is being reinvented and reconstructed against the backdrop of globalization, both locally and transnationally. Many of these constructions, however, echoes the colonial legacies.